Immunocompetent Expression of CD4+ T Cell and CD8+ T Cell, TNF-alpha and INF-gamma in Patient with Chronic Hepatitis C - Ellyza Nasrul (The Indonesian Society for Digestive Endoscopy, 2006)
Aim: To investigate the expression CD4+ T cell and CD8+ T cell as well as TNF-a and INF-g level on chronic hepatitis C. Methods: This is a cross-sectional study. Forty patients with chronic hepatitis C based on laboratory examination, who were collected from blood transfusion centers at Dr. M. Djamil Hospital. The control group used forty healthy samples. Results: There were 40 chronic hepatitis C cases satisfying the inclusion criteria. We found that CD4+ T cells count 50.35 ± 3.18%; CD8+ T cells count 59.37 ± 3.52%; TNF-a level 22.03 ± 3.72 pg/ml and INF-g level 4.47 ± 1.47 pg/ml. Conclusion: The chronic infection hepatitis C virus have given the effects on the immunocompetent cells which increased of CD4+, CD8+, TNF-a level and INF-g level. Keywords: hepatitis C virus, CD4+ T cell, CD8+ T cell, cytokines TNF-a, INF-g